Nutritional status of children with cerebral palsy in remote Sumba Island of Indonesia: a community-based key informants study. Issue 13 (19th June 2021) - Jahan, Israt; Muhit, Mohammad; Hardianto, Denny; Karim, Tasneem; Al Imam, Mahmudul Hassan; Das, Manik Chandra; Smithers-Sheedy, Hayley; Badawi, Nadia; Khandaker, Gulam
Abstract: Aim: To assess the burden and underlying factors of malnutrition among children with cerebral palsy (CP) in the remote Sumba Island, Indonesia. Methods: This is a community-based key informant (KI) method survey of children with CP in the southwest regency of Sumba Island, Indonesia (child population∼152 471). Children with suspected CP identified by trained community volunteers (KIs) underwent a detailed neurodevelopmental assessment by a multidisciplinary medical assessment team to confirm diagnosis of CP. Anthropometric measurements were taken, z scores were calculated, and nutritional status was determined following the World Health Organization guideline. Descriptive analyses were performed, multivariable linear regression model was fitted to identify potential predictors of malnutrition. Results: One hundred and thirty children with CP aged <18 years were included in the study. The majority were severely underweight (78.8%) and severely stunted (85.9%). Severe malnutrition was overrepresented among young children, children who had spastic tri/quadriplegia, Gross Motor Function Classification System levels III–V, had at least one associated impairment, speech impairment and/or swallowing difficulties. Age and presence of visual impairment were found to be significantly associated with weight-for-age z score (i.e., underweight) whereas, epilepsy was significantly associated with the height-for-age z score (i.e., stunting) when adjusted for other covariates. Conclusions: The substantial-high burden of malnutrition among children with CP in remote Sumba Island highlights their vulnerability to poor health-related outcomes. There is an urgent need for nutritional rehabilitation services to avert such consequences among children with CP in low and middle-income countries like Indonesia. Implications for rehabilitation: Malnutrition among children with cerebral palsy (CP) is alarmingly high in the remote Sumba island of Indonesia. Children with severe gross motor function limitations or spastic tri/quadriplegia had the most severe malnutrition. There is an urgent need for rehabilitation services including nutrition and feeding interventions for children with CP in low and middle-income countries like Indonesia.